Characterization of antibiotic resistance genes in soils from agroecosystems of the Brazilian Amazon - Tavares, Taynara Cristina Santos; Pinto, Lívia Freitas da Silva; Cardenas-Alegria, Oscar Victor; Dantas, Carlos William Dias; Silva, Sandro Patroca da; Ribeiro Cruz, Ana Cecília; do Rêgo, Aníbal Coutinho; Rogez, Hervé Louis Ghislain; Ramos, Rommel Thiago Juca; Faturi, Cristian; Nunes, Adriana Ribeiro Carneiro (Frontiers in Microbiology, 2025)
The conversion of forests to pastureland in the Amazon has increased over the years, resulting in significant impacts on ecosystem diversity, particularly on the soil microbiota. These changes affect the physical and biological properties of the soil, influencing the resistome and contributing to the selection and spread of antibiotic resistance genes (ARGs) in the soil environment. This study aimed to analyze the soil resistome under different managements in an Amazonian agrosystem. Soil samples were collected from the organic layer in forest and pasture areas within the municipality of São Miguel do Guamá, which included pastures managed with fertilization and those without the use of fertilizers. The samples underwent processing to extract genetic material and were sequenced using the Illumina platform. The sequences obtained were analyzed using bioinformatics tools to identify bacterial taxonomy and diversity. In addition, genetic annotation was performed using specialized databases to characterize functional genes, mobile elements, and resistance genes. The results showed changes in bacterial composition in pasture soils, where species such as Staphylococcus aureus, Staphylococcus cohnii, and Bacillus coagulans were more prevalent. In forest soils, differences in the composition of functional genes were detected, while soils without fertilizers exhibited a higher abundance of transposable elements. In addition, antibiotic resistance genes, such as macrolides, tetracyclines, aminoglycosides, among others, were more abundant in pasture soils.